Similar perspectives on prostate cancer screening value and new guidelines across patient demographic and PSA level subgroups: A qualitative study. (2nd November 2016) - Partin, Melissa R.; Lillie, Sarah E.; White, Katie M.; Wilt, Timothy J.; Chrouser, Kristin L.; Taylor, Brent C.; Burgess, Diana J.
Abstract: Background: In 2012, the United States Preventive Services Task Force (USPSTF) recommended against prostate‐specific antigen (PSA)‐based prostate cancer screening for all men. Objective: To inform educational materials addressing patient questions and concerns about the 2012 USPSTF guidelines, we sought to: (i) characterize patient perceptions about prostate cancer screening benefits, harms and recommendations against screening, and (ii) compare perceptions across race, age and PSA level subgroups. Methods: We conducted qualitative interviews with a sample of 26 men from the Minneapolis Veterans Affairs Health Care System, stratified by race (African American, other), age (50‐69, 70‐84) and PSA level (documented PSA level ≥4 in Veterans Health Administration electronic medical records vs no such documentation). We used an inductive approach informed by grounded theory to analyse transcribed interviews. Results: Most men in all subgroups expressed misperceptions about the benefits of prostate cancer screening and had difficulty identifying harms associated with screening. In all subgroups, reactions to recommendations against screening ranged from unconditionally receptive to highly resistant. Some men in every subgroup initially resistant to the idea said they would accept a recommendation to discontinue screening from their provider. Conclusions: Given the similarity of perceptions and reactions across subgroups, materials targeted by race, age and PSA level may not be necessary. Efforts to inform decision making about prostate cancer screening should address misperceptions about benefits and lack of awareness of harms. Provider perspectives and recommendations may play a pivotal role in shaping patient reactions to new guidelines.